2002
DOI: 10.1046/j.1365-2826.2002.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

The Affinity and Activity of the Multiple Hormone Response Element in the Proximal Promoter of the Human Oxytocin Gene

Abstract: In vivo there appears to be a marked association between oestrogen levels and the expression of the oxytocin (OT) gene in most tissues. Transfection and DNA-protein binding experiments using high levels of either oestrogen receptor (ER)alpha or ERbeta imply a direct interaction of these transcription factors with the multiple hormone response element (HRE) at approximately -160 from the transcription start site of the OT gene in most species. In an extensive set of experiments, we show, using both transfection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…In certain of these organs, estrogen regulates OT and/or OTR expression (15,16). Likewise, we found that OT is produced in abundance by bone marrow osteoblasts in response to estrogen, with the potential of exerting an anabolic effect on the skeleton (17).…”
mentioning
confidence: 64%
“…In certain of these organs, estrogen regulates OT and/or OTR expression (15,16). Likewise, we found that OT is produced in abundance by bone marrow osteoblasts in response to estrogen, with the potential of exerting an anabolic effect on the skeleton (17).…”
mentioning
confidence: 64%
“…To examine these in vivo associations, we performed a chromatin immunoprecipitation assay by using full-length hER␣ in MCF7 cells, spliceosome complex components, and a gene promoter region from human oxytocin that contained an estrogen-responsive element (26). Upon 17␤-estradiol (E2) stimulation, the SF3a subunits and hER␣ all were recruited to the oxytocin promoter along with RNA polymerase II (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, it was believed that OXT expression was directly regulated by the binding of estrogen to ERE in the promoter region (42,46). However, this mechanism is now in doubt as the ERE in the promoter of OXT is not a good match to the ERE consensus sequence (51,29). Induction of OXT Fig.…”
Section: Discussionmentioning
confidence: 99%